2020
DOI: 10.1177/1687814020945474
|View full text |Cite
|
Sign up to set email alerts
|

Tribological capabilities of chiral nematic liquid crystal additives in mineral motor oil

Abstract: This article presents the results of experimental investigation of tribological properties of commercial mineral motor oil with chiral nematic (also known as twisted nematic or cholesteric) liquid crystal additives. Cholesteryl stearate and valerate (fatty acid cholesterol esters) liquid crystals were used as oil additives in investigation. Tribological experiments were performed using a block-on-disc-type tribo-test machine at constant experiment time and sliding velocity conditions. The load (contact pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Regression modelling is an accepted method of characterizing tribological behaviour. [24][25][26] One of the advantages is that experimental data can be used to make predictions without reference to underlying metallurgical mechanisms. This approach is useful for the mechanical designer who may be interested to use a given material pair in applications.…”
Section: Linear Regression Model Fittingmentioning
confidence: 99%
“…Regression modelling is an accepted method of characterizing tribological behaviour. [24][25][26] One of the advantages is that experimental data can be used to make predictions without reference to underlying metallurgical mechanisms. This approach is useful for the mechanical designer who may be interested to use a given material pair in applications.…”
Section: Linear Regression Model Fittingmentioning
confidence: 99%
“…26,27 Unique schistose molecular structures provide greater shear resistance and are beneficial to form a large oil film when dissolved in oils. 28 The influence of temperature on tribological performance has been reported in several studies. Ermakov et al 29 found that cholesteric liquid crystal displayed the minimum coefficient of friction during the friction tests in the temperature range of mesophase.…”
Section: Introductionmentioning
confidence: 98%
“…Cholesteric liquid crystals can display excellent antifriction and antiwear properties in limited cases, ,, exhibiting different properties with the changes in temperature . Ester group in molecules can help to improve the solubility in oils. , Unique schistose molecular structures provide greater shear resistance and are beneficial to form a large oil film when dissolved in oils . The influence of temperature on tribological performance has been reported in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Yang's team [15] reported that 1,3-diketone EPND (1-(4-ethyl phenyl) nonane-1,3-dione), a nematic LC lubricant additive with excellent tribological properties, is particularly suitable for the severe operating conditions of low load and friction. Additionally, Mokshin [16] reported that cholesteryl stearate and fatty acid cholesterol esters LCs were used as lubricant additives. The tribological properties of LCs were evaluated, and the addition of LCs was found to significantly reduce the coefficient of friction (COF).…”
Section: Introductionmentioning
confidence: 99%